STUDI EKSPERIMEN KUAT LEKAT MORTAR BIASA PADA PASANGAN BETON RINGAN AERASI - Yulianto Hendra, Imam Muchoyar (Universitas Negeri Yogyakarta, 2014)
This study aims to determine the capacity of shear strength aerated lightweight concrete (AAC)with ordinary mortar and knowing the effective of mortar mix of aerated lightweight concrete.Aerated lightweight concrete is composed of a pair of aerated lightweight concrete usingordinary mortar binder. This research uses experimental study approach with 1PC:4 Ps; 1PC:5PS; 1PC: 6PS in proportion mix. The test object pair aerated lightweight concrete